Functional peptide-mediated plastid transformation in tobacco, rice, and kenaf - Odahara, Masaki; Horii, Yoko; Itami, Jun; Watanabe, Kenta; Numata, Keiji (Frontiers in Plant Science, 2022)
In plant engineering, plastid transformation is more advantageous than nuclear transformation because it results in high levels of protein expression from multiple genome copies per cell and is unaffected by gene silencing. The common plastid transformation methods are biolistic bombardment that requires special instruments and PEG-mediated transformation that is only applicable to protoplast cells. Here, we aimed to establish a new plastid transformation method in tobacco, rice, and kenaf using a biocompatible fusion peptide as a carrier to deliver DNA into plastids. We used a fusion peptide, KH-AtOEP34, comprising a polycationic DNA-binding peptide (KH) and a plastid-targeting peptide (AtOEP34) to successfully deliver and integrate construct DNA into plastid DNA (ptDNA) via homologous recombination. We obtained transformants in each species using selection with spectinomycin/streptomycin and the corresponding resistance gene aadA. The constructs remained in ptDNA for several months after introduction even under non-selective condition. The transformants normally flowered and are fertile in most cases. The offspring of the transformants (the T1 generation) retained the integrated construct DNA in their ptDNA, as indicated by PCR and DNA blotting, and expressed GFP in plastids from the integrated construct DNA. In summary, we successfully used the fusion peptide method for integration of foreign DNA in tobacco, rice, and kenaf ptDNA, and the integrated DNA was transmitted to the next generations. Whereas optimization is necessary to obtain homoplasmic plastid transformants that enable stable heterologous expression of genes, the plastid transformation method shown here is a novel nanomaterial-based approach distinct from the conventional methods, and we propose that this easy method could be used to target a wide variety of plants.